Competing Priorities : How Household Income Management Affects Women’s Microenterprises in Urban Ghana - Pierotti, Rachael (World Bank, Washington, DC, 2020)
Cash grants often lead to increases in business profits for male entrepreneurs, but not for female entrepreneurs. This study identifies key household-level factors that constrain women’s ability to grow their business. Through in-depth qualitative research, it provides evidence that intrahousehold relationships influence the business decisions of female microentrepreneurs in urban Ghana. Intrahousehold relationships constrain the decisions women make about their businesses in three primary ways: 1) women hide income and sometimes limit investment in an effort to reinforce their husband’s responsibilities as a primary provider and secure sufficient support, 2) women prioritize savings to meet daily household needs, cover shortfalls in their husband’s financial support, and take care of emergencies, and 3) marital insecurity encourages women to dedicate business income to long-term investments independent of their husbands, such as property or children’s’ education. Efforts to support women microentrepreneurs will need to address barriers to women’s ability to meet daily household needs and to plan for long-term security, in addition to relieving capital constraints. Policy responses could include increasing security by improving marital property rights for women or improving social safety nets to change the calculus that leads women to prioritize savings over investment.